Analisis kandungan total fenolik pada jonjot buah labu kuning (cucurbita moschata) - Dokri Gumolung (Jurnal Kimia Fullerene, 2018)
The purpose of this study was to identify the total phenolic compound extract of pumpkin fruit strands. Pumpkin is a food rich in vitamin A and C, minerals, and phenolic compounds. Pumpkin plant as a minor food commodity, it is very rich in bioactive compounds that act as antioxidant very useful for human health. Strands in yellow fruit processing is often used as waste. This research was conducted by using the method of laboratory analysis through stages, determination and sampling, sample preparation, analysis of phenolic compound content in extract determined by Folin-Ciocalteu method and phenolic content calculation. The results showed that yellow pumpkin strands had total phenolic content 167,85 mg / kg in ethanol extract and 15,20 mg / kg in Petroleum ether extract. The data showed that the highest total phenolic content was found in the ethanol extract 167,85 mg / kg. This is because polar ethanol solvent can dissolve the polar compound.